2015
DOI: 10.1590/01000683rbcs20140818
|View full text |Cite
|
Sign up to set email alerts
|

Biochar: Pyrogenic Carbon for Agricultural Use - A Critical Review

Abstract: Biochar (carbonized biomass for agricultural use) has been used worldwide as soil amendment and is a technology of particular interest for Brazil, since its "inspiration" is from the historical Terra Preta de Índios (Amazon Dark Earth), and also because Brazil is the world's largest charcoal producer, generating enormous residue quantities in form of fine charcoal and due to the availability of different residual biomasses, mainly from agroindustry (e.g., sugar-cane bagasse; wood and paper-mill wastes; residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
29

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(121 citation statements)
references
References 189 publications
(245 reference statements)
2
77
0
29
Order By: Relevance
“…With pyrolysis temperature at 650˚C, aliphatic chains, aromatic rings and elemental composition of C, N and O are reduced, making the biochar more recalcitrant [44]. Many characteristics, such as ash content, CEC and C/N ratio, vary according to the raw material [45] and [46], which justifies similar CO 2 emission values for the BCS, whether pyrolyzed at 350˚C or 650˚C. The BCS material is already highly recalcitrant, producing a biochar with lower ash content, lower nutrient diversity and greater surface area [47].…”
Section: Discussionmentioning
confidence: 99%
“…With pyrolysis temperature at 650˚C, aliphatic chains, aromatic rings and elemental composition of C, N and O are reduced, making the biochar more recalcitrant [44]. Many characteristics, such as ash content, CEC and C/N ratio, vary according to the raw material [45] and [46], which justifies similar CO 2 emission values for the BCS, whether pyrolyzed at 350˚C or 650˚C. The BCS material is already highly recalcitrant, producing a biochar with lower ash content, lower nutrient diversity and greater surface area [47].…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale application of biochar in agriculture has been proposed as a promising technology for long-term C-sequestration and underground storage [104,105]. At the same time, much research and many (though not all) experimental applications of charcoal have demonstrated positive effects of black carbon on soil physical properties, including pore space; bulk density; water retention and infiltration [102,106,107]; soil chemical characteristics, such as a long-term increase in the cation exchange capacity [108,109], nutrient retention [110], improved P availability [111,112] (but frequently reduced N-availability [113], and reduced methane and nitrous oxide emissions [114][115][116] (but see [117,118]). Biochar applications have also been reported beneficial for soil biology, such as increases in mycorrhizal fungi [119] and in biological N 2 -fixation [120] (but see [121] and increases in overall diversity of the microbiota [103,122,123], despite the possible toxic nature of some biochar compounds [124].…”
Section: Biochar and Indian Blacksoilsmentioning
confidence: 99%
“…Dentre diversos interesses no uso desse produto deve-se destacar o seu potencial para mitigar efeitos das mudanças climática, potencial para melhoria na fertilidade dos solos e crescimento de cultivos, retenção de água, e mais recentemente controle de poluição do solo (NOVOTNY et al, 2015) (Figura 5). Os estudos sobre biocarvão nascem de investigações sobre a matéria orgânica das Terras Pretas de Índio (TPI), em consonância com questionamentos que envolvem o manejo sustentável de solos, mudanças climáticas globais e estoque de carbono (LEHMANN et al, 2009).…”
Section: Biocarvãounclassified
“…Essas características diferenciadas em comparação com os demais solos da região amazônica são atribuídas à presença de material carbonizado com a presença de grupos funcionais químicos e estrutura física específica (NOVOTNY et al 2009). Nesse contexto, surge o biocarvão, produzido com o objetivo de ser aplicado ao solo para mitigar mudanças climáticas e melhorar desempenho agrícola (SOHI et al, 2010;NOVOTNY et al, 2015).…”
Section: Biocarvãounclassified
See 1 more Smart Citation